PERAN KEPUASAN PELANGGAN MEMEDIASI PENGARUH KUALITAS PELAYANAN TERHADAP RE-VISIT INTENTION PADA HOTEL GRAND INNA KUTA - Dewantara, I Dewa Gede Brahmanta; Aksari, Ni Made Asti (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.10.TAHUN.2023DO - 10.24843/EEB.2023.v12.i10.p11, 2023)
Hotels must pay attention to customer satisfaction because when customers are satisfied it affects their intention to re-visit the place. The purpose of this study is to explain the role of customer satisfaction in mediating the effect of service quality on re-visit intention. This research was conducted at the Grand Inna Kuta Hotel. Samples were taken as many as 100 respondents through purposive sampling method and distributed using google form questionnaires with criteria that have been adjusted and measured by 18 indicators using a Likert scale. The data was analysed using path analysis and Sobel test. The results of this study indicate that all hypotheses are accepted. Service quality has a positive and significant effect on re-visit intention and customer satisfaction, customer satisfaction has a positive and significant effect on re-visit intention, and customer satisfaction partially mediate the effect of service quality towards re-visit intention. This implies that t o create re-visit intention, Grand Inna Kuta Hotel needs to pay attention to customer satisfaction and the quality of services it provides.